2021
DOI: 10.1101/2021.04.28.441816
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

No reproductive fitness benefits of dear enemy behaviour in a territorial songbird

Abstract: Territorial animals often exhibit the dear enemy effect, in which individuals respond less aggressively to neighbours than to other individuals. The dear enemy effect is hypothesized to be adaptive by reducing unnecessary aggressive interactions with individuals that are not a threat to territory ownership. A key prediction of this hypothesis, that individual fitness will be affected by variation in the speed and extent to which individuals reduce their aggression towards neighbours relative to strangers, has … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 145 publications
0
1
0
Order By: Relevance
“…We had genetic information (i.e. microsatellite markers) for 15 of these 19 individuals and most of their parents (Reichert et al 2021), which revealed one case in which the social and the biological father did not match (extra-pair paternity), but the latter could be identified and corrected in the final dataset. For the four individuals lacking genetic data, we assumed the social father was the biological father.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…We had genetic information (i.e. microsatellite markers) for 15 of these 19 individuals and most of their parents (Reichert et al 2021), which revealed one case in which the social and the biological father did not match (extra-pair paternity), but the latter could be identified and corrected in the final dataset. For the four individuals lacking genetic data, we assumed the social father was the biological father.…”
Section: Statistical Analysesmentioning
confidence: 99%